1999
DOI: 10.1111/j.1467-842x.1999.tb01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Falls among healthy, community-dwelling, older women: a prospective study of frequency, circumstances, consequences and prediction accuracy

Abstract: Objective: Most studies of falls among older people have focused on those with some degree of balance or mobility impairment. This study aimed to establish whether falls and associated injuries were a major problem among healthy, older women, whether there were some common features in the falls, and whether these falls could be accurately predicted. Method: Ninety‐six healthy, active community‐dwelling women in Melbourne, Australia, aged at least 70 years (mean 74.1 ±4.0) were initially measured on a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
211
3
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(232 citation statements)
references
References 39 publications
11
211
3
7
Order By: Relevance
“…Health and economic aspects of fall interventions necessitate the identification of and intervention for individuals at greatest risk of falling (Hill et al, 1999;National Aging Research Institute, 2000). In that regard, various measures of balance and physical functions have been proposed to identify potential fallers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health and economic aspects of fall interventions necessitate the identification of and intervention for individuals at greatest risk of falling (Hill et al, 1999;National Aging Research Institute, 2000). In that regard, various measures of balance and physical functions have been proposed to identify potential fallers.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies suggested that traditional linear measures mask the dynamic structure of motor variability such as the loss of the temporal variations of the gait pattern due to averaging procedures. Measures of static equilibrium during quiet standing are useful estimates of risk (Hill et al, 1999) but cannot fully characterize stability during walking wherein the majority of falls occur (Campbell et al, 1981). Nonlinear stability assessments of walking may augment traditional clinical assessments to help identify potential fallers.…”
Section: Discussionmentioning
confidence: 99%
“…The pads are held in position by being incorporated into a garment that is supposed to keep the pad in the right position with respect to the hip area. Unfortunately, it often fails to do so because the pocket containing the pad can move away from the area during falls [11]. Additionally, some seniors refuse to use hip protectors because they find them constraining their daily activities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Balance impairment is also associated with the deconditioning of the cardiovascular and musculoskeletal systems and the aging process [4][5][6] Postural instability (increased postural sway) has been demonstrated in apparently healthy individuals after 40 years of age and among the elderly [3]. A direct link has been found between postural instability and unexplained falls among the elderly [6,7].…”
Section: Introductionmentioning
confidence: 99%